2022
DOI: 10.3389/fgene.2022.805709
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hemoglobin-S and Baseline Level of Knowledge on Sickle Cell Disease Among Pregnant Women Attending Antenatal Clinics in Dar-Es-Salaam, Tanzania

Abstract: Background: Sickle cell disease (SCD) is the single most important genetic cause of childhood mortality globally. Newborn screening (NBS) is the recommended intervention aimed at early identification of babies with SCD and their linkage to care. To ensure success of NBS, pregnant women need to have the required knowledge on SCD and therefore motivation to screen their babies.Objective: The aim of this study was to determine the prevalence of hemoglobin-S and assess the baseline level of knowledge on SCD among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Despite the high prevalence of SCD in Tanzania (13-20%) (3,4), only 2 participants knew their SCD status before intervention (11). This was quiet similar to many other studies which showed low awareness of personal SCD status among different groups (8, 9, 11, 13).…”
Section: Discussionsupporting
confidence: 81%
“…Despite the high prevalence of SCD in Tanzania (13-20%) (3,4), only 2 participants knew their SCD status before intervention (11). This was quiet similar to many other studies which showed low awareness of personal SCD status among different groups (8, 9, 11, 13).…”
Section: Discussionsupporting
confidence: 81%
“…The ANCs have been successfully utilized in providing health education on HIV and other conditions [ 16 – 19 ], and thus success in proving health education on SCD opens the possibility to consider integrating health education on SCD into the comprehensive care package for pregnant women [ 10 ], particularly in areas with high prevalence of SCD. Before health education intervention, the level of knowledge among pregnant women in our cohort was significantly predicted by the level of education, hearing of SCD at school and having lived with a patient with SCD [ 20 ]. However, following health education intervention, the efficacy of the intervention was only predicted by having shared the received information with others.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study has shown that families understanding of the results provided is still challenging. This observation suggests that despite the high birth prevalence of SCD in the area, still knowledge on the disease is very low (Abioye-Kuteyi et al, 2009;Ezenwosu et al, 2015;Obed et al, 2017;Tutuba et al, 2022). One of the recommendations to address this is to increase public awareness through cultural respectful advocacy campaigns within the communities (Anie et al, 2016;Brown, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This will ensure mothers receive adequate education on the SCD and SCT and do understand implications of having a child with either of the two. Others suggested to start providing the health education programs during antenatal clinics where uptake/ attendance is very good and great possibility of finding both parents (Tutuba et al, 2022). Others have suggested counselling and education programs to be offered soon after screening (Ojodu, 2014).…”
Section: Discussionmentioning
confidence: 99%